The quality of life and coping skills of patients with human immunodeficiency virus among different occupation - Kamthan, Shivam; Pant, Bhawna; Kumar, Deepak; Gupta, Monika; Nasser, Kaynat (International Journal Of Community Medicine And Public Health, 2019)
Background: Nowadays, HIV and AIDS has become an important public health issue across the world. Quality of life (QOL) is an important tool to assess general wellbeing of HIV patients. Coping skills are the psychological skills to face the difficult situations like HIV or AIDS. The workplace plays an important role in determining general wellbeing and the psychological problems in HIV patients. Therefore, it is very important to assess the quality of life and coping skills of HIV patients among different occupations. Methods: A cross-sectional study consisting of conveniently selected 200 HIV patients was conducted at ART center LLRM Medical College, Meerut. The study subjects were interviewed by using questionnaire consisting of WHOQOL HIV BREF (WHO quality of life questionnaire) and Brief-COPE scale questionnaires. Descriptive statistics and ANOVA test were used for analysis of the data. Results: 36% of HIV patients were housewives and 26.5 % of HIV patients were drivers. The quality of life score was higher in HIV patients who were in unemployed (14.98) and farmers (14.49) whereas was lowest in all others category (10.73). The housewives, farmers, government jobs or service, drivers and other had maximum adaptive coping in religion and minimum adaptive coping in humour. There was no uniform pattern of maladaptive coping skills of HIV patients among different occupations. Conclusions: Quality of life score was better in HIV patients who were unemployed and farmers as compared to HIV patients who were drivers, housewives, government jobs or service. Religion was most effective adaptive coping strategy and humour was least effective adaptive coping strategy in HIV patients.